2015
DOI: 10.1021/acs.jpcc.5b00445
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Carbon Nanotubes/Amorphous Porous Carbon Nanocomposite: A Molecular Simulation Study

Abstract: A nanocasting method in molecular dynamics (MD) simulation was developed to mimetically synthesize nanocomposites that contain aligned carbon nanotubes (CNTs) as fillers in an amorphous porous carbon (a-PC) matrix. Structural features of aligned CNTs/a-PC nanocomposites such as the crystallinity of the CNT and the matrix as well as the interfacial bond density between these two components can be controlled by the synthesis parameters, for instance, (i) the interaction strength between a template and carbon ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For instance, a higher carbon source gas feed rate results in blockage of the voids and surface of the CNT preform in a short time by the initial PyC that inevitably impacts the following densification process. Several studies reported the epitaxial growth of PyC around CNTs that may help figure out the carbon deposition mechanism via the CVI technique. ,,,, Additionally, theoretical predictions on the structure evolution of CNT/C composites via the CVI technique under different processing conditions (including parameters mentioned above) are in high demand that could effectively guide experimental efforts. …”
Section: Preparation Of Cnt/c Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a higher carbon source gas feed rate results in blockage of the voids and surface of the CNT preform in a short time by the initial PyC that inevitably impacts the following densification process. Several studies reported the epitaxial growth of PyC around CNTs that may help figure out the carbon deposition mechanism via the CVI technique. ,,,, Additionally, theoretical predictions on the structure evolution of CNT/C composites via the CVI technique under different processing conditions (including parameters mentioned above) are in high demand that could effectively guide experimental efforts. …”
Section: Preparation Of Cnt/c Compositesmentioning
confidence: 99%
“…(g) Modulus variations while increasing the lateral CNT spacing of L CNT from 4 to 6 nm. Reproduced from ref . Copyright 2015 American Chemical Society.…”
Section: Mechanical Reinforcement Mechanism Of Cnt/c Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…sinusoidal or helical, [14][15][16][17][18][19] or neglected altogether. [20][21][22][23][24][25][26] This stems in part from the lack of an accessible theoretical framework that can be used to quantify the impact of waviness on the packing morphology of real NFs in three-dimensions. In this report, we use a simulation framework in conjunction with an existing continuous coordination number theoretical framework to evaluate the influence of NF waviness on the morphology of an exemplary NF system, carbon nanotube (CNT) arrays.…”
mentioning
confidence: 99%
“…This indicates the increased volume of the different physical states at the interfaces of the matrix surrounded by functional nanomaterials. 54 The higher degree of thermal conductivities in the composite reinforced with 3D carbonaceous assemblies could be explained by the morphological rearrangement. The reconstruction results in highly plasticized amorphous regions in the resin matrix which has been manifested by the DMA and TMA experiments (Figure 4).…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%